Complex permittivity and microwave absorption properties of OPEFB fiber–polycaprolactone composites filled with recycled hematite (α-Fe2O3) nanoparticles - Mensah, Ebenezer Ekow; Abbas, Zulkifly; Azis, Raba'ah Syahidah; Ibrahim, Nor Azowa; Khamis, Ahmad Mamoun (MDPI, 2019)
Recycled hematite (α-Fe2O3) nanoparticles with enhanced complex permittivity properties have been incorporated as a filler in a polycaprolactone (PCL) matrix reinforced with oil palm empty fruit bunch (OPEFB) fiber for microwave absorption applications. The complex permittivity values were improved by reducing the particle sizes to the nano scale via high-energy ball milling for 12 h. A total of 5–20 wt.% recycled α-Fe2O3/OPEFB/PCL nanocomposites were examined for their complex permittivity and microwave absorption properties via the open ended coaxial (OEC) technique and the transmission/reflection line measurement using a microstrip connected to a two-port vector network analyzer. The microstructural analysis of the samples included X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM) and Fourier transform infrared spectroscopy (FTIR). At 1 GHz, the real (ε′) and imaginary (ε″) parts of complex permittivity of recycled α-Fe2O3 particles, respectively, increased from 7.88 to 12.75 and 0.14 to 0.40 when the particle size was reduced from 1.73 μm to 16.2 nm. A minimum reflection loss of −24.2 dB was achieved by the 20 wt.% nanocomposite at 2.4 GHz. Recycled α-Fe2O3 nanoparticles are effective fillers for microwave absorbing polymer-based composites in 1–4 GHz range applications.